Safety of weevil resistant sweetpotato varieties - International Potato Center (2011)
Genetically modified (GM) crops contain traits that have been introduced by the tools of modern biotechnology. Their novelty has prompted comprehensive assessment of their human and environmental safety. With conventional breeding, thousands of genes are shuffled and recombined to obtain a desired trait. In comparison, modern biotechnology adds as little as one single gene to provide the desired trait to an existing well-performing variety. As a result, the level of genetic modification is only a tiny fraction of that produced through conventional breeding. However, a widespread lack of familiarity with biotechnology has led to consumer demands for sophisticated safety risk assessments.